Pelatihan Pembuatan Google Form bagi Guru SD Sebagai Media Evaluasi Pembelajaran Jarak Jauh (PJJ) Masa Pandemi - Rifky Maulana Yusron; Rica Wijayanti; Anindita Trinura Novitasari (Prodi PGSD FIP UNM, 2020)
Distance Learning (PJJ) began to be applied by all teachers in Indonesia during the Covid Pandemic including teacher who taughtat the Elementary School (SD) level. The application of this learning is not as easy as what many people talk about, because teachers must be able to select and design instrucctional media using technology. The problem ezperienced by teacher, especially in the regions, is the lack of knowledge in making technology-based learning media, especially learning media that can be used as an evaluation material for Distance Learning (PJJ). As a solution tothis problem, our team conducted training on making google forms for elementary teachers as a medium for evauating Distance Learning (PJJ) during the pandemic. The ethod we provide for this community service activity is by providing direct training to elementary school teachers, making simole modules, and providing assitance in making google form evaluation media. The result of this services activity is that as many as 20 teachers who participated in the training were able to create and design their own google form according to the needs of each subject as a media for evaluation of Distance Learing (PJJ. In addition, based on the results of the questionnaire filled out by the teachers who attended the training, it shows that 90% of the teachers understand how to make google forms themselves and 100% of the teachers are happy with the training acivities that have been held.Keyword: google form, pjj, evaluation learning